The Students’ Interest in Learning English at SMA Negeri 1 Mowewe Kolaka Timur - Suharvina Suharvina; A. Muliati; M. Tahir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The purpose of this study was to determine students' interest in learning English. This study uses a quantitative method. The researchers chose class X MIA 1 SMA Negeri 1 Mowewe Kolaka Timur which consisted of 40 students. The research instrument is a questionnaire. The results showed that the general interest of students was a moderate category towards students interested in learning English. This is supported by the results of data analysis obtained from the questionnaire and types of interest. the results of the questionnaire interest have a moderate category. the type of manifester interest is included in the very strong category. The author concludes that the student's interest in learning English in class X MIA 1 is still low. Teachers must create a comfortable environment during the teaching and learning process of English.